Bionic Silk Fibroin Film Induces Morphological Changes and Differentiation of Tendon Stem/Progenitor Cells. (2nd December 2020) - Lu, Kang; Chen, Xiaodie; Tang, Hong; Zhou, Mei; He, Gang; Liu, Juan; Bian, Xuting; Guo, Yupeng; Lai, Fan; Yang, Mingyu; Lu, Zhisong; Tang, Kanglai
Abstract : Purpose . Tendon injuries are common musculoskeletal system disorders, but the ability for tendon regeneration is limited. Silk fibroin (SF) film may be suitable for tendon regeneration due to its excellent biocompatibility and physical properties. This study is aimed at evaluating the application value of bionic SF film in tendon regeneration. Methods . Tendon stem/progenitor cells (TSPCs) were isolated from rat Achilles tendon and characterized based on their surface marker expression and multilineage differentiation potential. SF films with smooth or bionic microstructure surfaces (5, 10, 15, 20  μ m) were prepared. The morphology and mechanical properties of natural tendons and SF films were characterized. TSPCs were used as the seed cells, and the cell viability and cell adhesion morphology were analyzed. The tendongenesis-related gene expression of TSPCs was also evaluated using quantitative polymerase chain reaction. Results . Compared to the native tendon, only the 10, 15, and 20  μ m SF film groups had comparable maximum loading and ultimate stress, with the exception of the breaking elongation rate. The 10  μ m SF film group had the highest percentage of oriented cells and the most significant changes in cell morphology. The most significant upregulations in the expression of COL1A1, TNC, TNMD, and SCX were also observed in the 10  μ m SF film group. Conclusion . SF film with a bionic microstructure can serve as a tissue engineering scaffold and provide biophysical cues for the use of TSPCs to achieve proper cellular adherence arrangement and morphology as well as promote the tenogenic differentiation of TSPCs, making it a valuable customizable biomaterial for future applications in tendon repair.